The impact of SGLT2 inhibition on imaging markers of cardiac function: A systematic review and meta-analysis - Panagiotis Theofilis; Alexios S. Antonopoulos; Themistoklis Katsimichas; Evangelos Oikonomou; Gerasimos Siasos; Constantina Aggeli; Konstantinos Tsioufis; Dimitris Tousoulis (Elsevier, 2022)
Objectives: The use of sodium-glucose cotransporter-2 inhibitors (SGLT2-Is) has resulted in significant benefits in patients with heart failure irrespective of left ventricular ejection fraction (LVEF) and the presence of diabetes mellitus. The aim of this systematic review and meta-analysis was to assess the impact of SGLT2-Is on cardiac function indices. Methods: We conducted a systematic literature search for studies assessing the changes in LVEF, global longitudinal strain (GLS), left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), left ventricular mass index (LVMi), left atrial volume index (LAVi), and E/e' following the initiation of an SGLT2-I. Results: A total of 32 studies with 2351 patients were included. SGLT2 inhibition resulted in a significant improvement of LVEF [MD 1.97 (95%CI 0.92, 3.02), p < .01, I2:84%] in patients with heart failure, an increase in GLS [MD 1.17 (95% CI 0.25, 2.10), p < .01], a decrease in LVESV [MD: −3.60 (95% CI −7.02, −0.18), p = .04, I2:9%] while the effect was neutral concerning LVEDV [MD: −3.10 (95% CI −6.76, 0.56), p = .40, I2:4%]. LVMi [MD: −3.99 (95% CI −7.16 to −0.82), p = .01, I2:65%], LAVi [MD: −1.77 (95% CI −2.97, −0.57), p < .01, I2:0%], and E/e' [MD: −1.39 (95% CI −2.04, −0.73), p < .01, I2:55%] were significantly reduced. Conclusions: In this systematic review and meta-analysis, the use of SGLT2 inhibitors was associated with an improvement in markers of cardiac function, confirming the importance of SGLT2 inhibition towards the reversal of cardiac remodeling.